Heterogeneidade Estrutural e a Dinâmica da Produtividade do Trabalho: Uma Análise por porte da indústria de transformação brasileira - Silva, Ariana Cericatto da (2021)
The main objective of this Thesis was to verify the existence and permanence of structural heterogeneity (SH) between and within sizes of Brazilian industrial companies, based on the analysis of the evolution of labor productivity. For this, through a special tabulation of the Annual Industrial Survey, from 1997 to 2018, a descriptive analysis was used to build an overview of companies and their sizes and the shift-share analysis to decompose productivity growth of the work of the manufacturing industry between and within companies' sizes. In addition, econometric methods were used - panel data regression with fixed and random effects and quantile regression - with the use of a special tabulation with a crossing of the Annual Industrial Survey and Innovation Survey databases, to the years 2008, 2011, 2014 and 2017. Through the results, it was found that there was a reduction in SH between sizes, from 2007, with the growth of productivity of small and medium-sized companies and the fall of large companies. The increase in labor productivity among small companies was driven by the manufacturing of other transport equipment and the production of coke, petroleum refining, elaboration of nuclear fuels and alcohol production, which also showed an increase in the number of people employed in this size range of company. It was evident that between 1997 and 2018, there was an increase in productive inequality in each size, but between sizes they came closer, which indicates a reduction in SH between sizes. The empirical analysis showed different behaviors among the explanatory variables in relation to labor productivity. As the total spending on R&D that seems to have more importance among manufacturing industry sectors than among company sizes. Thus, it is considered that the evidence identified contributes to the discussion of the topic of SH in the Brazilian manufacturing industry, especially in the national literature on the understanding of the dynamics of SH, when considering the differences between and within company sizes.